Grid converters for photovoltaic and wind power systems - Teodorescu, Remus (IEEE Wiley, 2011)
"Grid Converters for Photovoltaic and Wind Power Systems provides a comprehensive description of the control of grid converters for photovoltaic and wind power systems. The authors present a range of control methods for meeting the latest application, power quality and power conversion requirements and standards, as well as looking towards potential future control functions. Practical examples, exercises, and an accompanying website with simulation models using Matlab and Simulink environments, and PSIM software make this text a pragmatic resource for electrical engineers as well as students taking related courses"